2017
DOI: 10.18632/oncotarget.17646
|View full text |Cite
|
Sign up to set email alerts
|

A cancer vaccine based on fluorine-modified sialyl-Tn induces robust immune responses in a murine model

Abstract: Development of an effective vaccine to target tumor associated carbohydrate antigens, aberrantly expressed on the cell surface of various carcinomas, is an appealing approach toward cancer immunotherapy. However, a major problem of carbohydrate antigens is their poor immunogenicity. Immunization with modified-carbohydrate antigens could improve the immunogenicity and induce cross reaction with the native carbohydrate antigens. In this study, we investigated the antitumor ability of three fluoro-substituted sia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 44 publications
(59 reference statements)
0
30
0
Order By: Relevance
“…As any antigen that is perceived as non-self will be sufficient to induce an immune response, there is a vast array of known proteins at our disposal to use as carrier. For example, keyhole limpet hemocyanin has been used as a carrier for glycoconjugate vaccines against Candida albicans (Liao et al, 2016) and even some cancers with distinct molecular markers (Song, Zheng, Liu, Zhou, & Ye, 2017). Bovine serum albumin (BSA) is a wellcharacterised protein that has also been used, for example against Aspergillus fumigatus (Komarova et al, 2015).…”
Section: Pathways To Conjugationmentioning
confidence: 99%
“…As any antigen that is perceived as non-self will be sufficient to induce an immune response, there is a vast array of known proteins at our disposal to use as carrier. For example, keyhole limpet hemocyanin has been used as a carrier for glycoconjugate vaccines against Candida albicans (Liao et al, 2016) and even some cancers with distinct molecular markers (Song, Zheng, Liu, Zhou, & Ye, 2017). Bovine serum albumin (BSA) is a wellcharacterised protein that has also been used, for example against Aspergillus fumigatus (Komarova et al, 2015).…”
Section: Pathways To Conjugationmentioning
confidence: 99%
“…Recently, a fluoro‐substituted STn analogue coupled to KLH was found to induce robust immune responses in a tumor‐bearing murine model. This vaccine candidate could mediate complement‐dependent cytotoxicity and antibody‐dependent cell‐mediated cytotoxicity against human tumor cells, and it seemed a superior in tumor prevention . Several STn derivatives with N ‐acetyl modifications were synthesized, they were then incorporated into a MUC1 peptide and were further connected to KLH.…”
Section: Advances In Tacas Based Cancer Vaccinesmentioning
confidence: 99%
“…This vaccine candidate could mediate complement-dependent cytotoxicity and antibody-dependent cell-mediated cytotoxicity against human tumor cells, and it seemed a superior in tumor prevention. 204 Several STn derivatives with N-acetyl modifications were synthesized, they were then incorporated into a MUC1 peptide and were further connected to KLH. The evaluation results of the synthetic vaccine conjugates demonstrated that the carbohydrate antigen modification strategy has the potential to improve immunogenicity of natural MUC1 glycopeptides.…”
Section: Cross-reactivity-based Cancer Vaccinesmentioning
confidence: 99%
“…The disaccharide Neu5Acα2–6GalNAcα1- O -Ser/Thr is a common short O -glycan TACA conjugated to proteins, also referred to as sialyl-Tn (STn; AcSTn). While this is a rare antigen or occluded in normal tissues due to further O -acetylation of the sialic acid (Sia) 3 , it is present in more than 80% of human carcinomas 13 , including those of the pancreas, breast, prostate, ovaries and colorectum 14 , 15 . Cells expressing the STn antigen have reduced adherence to extracellular matrix components, and show higher migration rates, thus promoting metastasis 16 .…”
Section: Introductionmentioning
confidence: 99%